2020
DOI: 10.2147/rmhp.s280952
|View full text |Cite
|
Sign up to set email alerts
|

<p>When Politics Meets Pandemic: How Prime Minister Netanyahu and a Small Team Communicated Health and Risk Information to the Israeli Public During the Early Stages of COVID-19</p>

Abstract: Background The coronavirus brought the world’s leaders to the center of the media stage, where they not only managed the COVID-19 pandemic but also communicated it to the public. The means they used to communicate the global pandemic reveal their strategies and the narratives they chose to create in their nation’s social consciousness. In Israel, the crisis broke out after three election cycles, such that the government in charge of the crisis was an interim government under the leadership of Prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…When faced with a novel disease such as COVID-19, people may try to draw comparisons to various other diseases ( Atkinson et al, 2020 ; Gesser-Edelsburg and Hijazi, 2020 ; De Ridder, 2020 ). Such comparisons could have implications for their motivations to implement protective behaviors ( Edwards, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When faced with a novel disease such as COVID-19, people may try to draw comparisons to various other diseases ( Atkinson et al, 2020 ; Gesser-Edelsburg and Hijazi, 2020 ; De Ridder, 2020 ). Such comparisons could have implications for their motivations to implement protective behaviors ( Edwards, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons between COVID-19 and other diseases also appeared in the public discourse. Policymakers and health care providers in Israel and the UK used comparisons to pandemic rather than seasonal influenza ( Atkinson et al, 2020 ; Gesser-Edelsburg and Hijazi, 2020 ). An analysis of Flemish newspaper articles published early in the pandemic found that COVID-19 was compared with pandemic influenza (Spanish flu, H1N1), SARS, MERS, and Ebola ( De Ridder, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, most health organizations, and mainly governmental organizations, are still quite based on an organizational structure that is primarily hierarchical and much less cooperative and democratic, and this structure affects how information is processed and disseminated. 116 Second, many public health employees in key positions in government and health organizations still use paternalistic thought patterns. In addition, the experts who manage the policy of government ministries perceive any disagreements in how they chart government policy as a threat to their professional status.…”
Section: Discussionmentioning
confidence: 99%
“…This approach often conflicts with the essence of scientific language as a language of inquiry and doubt that communicates uncertainty wherever it exists. 116 …”
Section: Path 2: Strategies For Enabling Health Organizations To Respond On Social Networkmentioning
confidence: 99%
“…Indeed, when the COVID-19 pandemic began, Israel was being governed by an interim prime minister operating under three criminal indictments, after three election cycles. 46 , 47 The pandemic generated a multidimensional crisis in Israel that undermined economic and social resilience, challenged effective governance and even provided a cover for processes that had the potential to harm democratic values.…”
Section: Introductionmentioning
confidence: 99%